Intake, digestibility, and ingestive behavior of sheep fed with thornless Mandacaru, cactus pear genotypes Orelha de Elefante Mexicana and Miúda - Maria Vitória Serafim da Silva; Emerson Moreira de Aguiar; José Geraldo Medeiros da Silva; Airon Aparecido Silva de Melo; Daniel Barros Cardoso; Marcone Geraldo Costa; José Hamilton da Costa Filho; Adriana Margarida Zanbotto Ramalho (Acta Scientiarum. Animal Sciences, 2022)
This study aimed to evaluate the intake, digestibility, and ingestive behavior of sheep fed with different species of forage cacti. Fifteen sheep (17.27kg ± 1 kg) were distributed in a completely randomized experimental design with three treatments and five replicates. The treatments were diets on a dry matter basis composed of 430.9 g kg-1 of thornless Mandacaru cactus (Cereus hildmannianus), 525.7 g kg-1 of cactus pear cv. Orelha de Elefante Mexicana (Opuntia stricta) and 492.1 g kg-1 of cactus pear cv. Miúda (Nopalea cochenillifera) in addition to Sabiá hay (Mimosa caesalpiniaefolia) (194.7 to 233.8 g kg-1), plus concentrate feed. The intake of the dry matter, organic matter, ether extract, neutral detergent fiber, total carbohydrates, non-fiber carbohydrates, total digestible nutrients and voluntary water intake in g day-1 was not differ (p > 0.05) by experimental diets. There were no differences (p > 0.05) in digestibility coefficients of the dry matter, organic matter, neutral detergent fiber, total carbohydrates, non-fiber carbohydrates, and total digestible nutrients between the experimental diets. The feeding times differed (p < 0.05) between diets, with a higher value for the Opuntia diet, while the rumination times, feeding efficiency, and rumination efficiency did not differ (p > 0.05). The cactus Cereus and Opuntia and Nopalea have similar nutritional value in sheep’s diet.